Sequence Comparison of Human and Mouse Genes Reveals a Homologous Block Structure in the Promoter Regions - Suzuki, Yutaka; Yamashita, Riu; Shirota, Matsuyuki; Sakakibara, Yuta; Chiba, Joe; Mizushima-Sugano, Junko; Nakai, Kenta; Sugano, Sumio (Genome Research, 2004)
Comparative sequence analysis was carried out for the regions adjacent to experimentally validated transcriptional start sites (TSSs), using 3324 pairs of human and mouse genes. We aligned the upstream putative promoter sequences over the 1-kb proximal regions and found that the sequence conservation could not be further extended at, on average, 510 bp upstream positions of the TSSs. This discontinuous manner of the sequence conservation revealed a “block” structure in about one-third of the putative promoter regions. Consistently, we also observed that G+C content and CpG frequency were significantly different inside and outside the blocks. Within the blocks, the sequence identity was uniformly 65% regardless of their length. About 90% of the previously characterized transcription factor binding sites were located within those blocks. In 46% of the blocks, the 5′ ends were bounded by interspersed repetitive elements, some of which may have nucleated the genomic rearrangements. The length of the blocks was shortest in the promoters of genes encoding transcription factors and of genes whose expression patterns are brain specific, which suggests that the evolutional diversifications in the transcriptional modulations should be the most marked in these populations of genes.
10.1101/gr.2435604